PERKEMBANGAN BAHASA ANAK SD NEGERI DI KECAMATAN MEDAN TIMUR KOTA MEDAN SUMATERA UTARA - Silaban, Awy; Br Ginting, Gracia Tri Putri; Hutapea, Maykhel Yustinus; Siregar, Mutia Haryani; Priska, Nadia; Kalsum, Ummi (Universitas Negeri Medan, 2023)
Language is a communication tool that one person conveys to another person in order to know what the aims and objectives are. The importance of language as a human identity cannot be separated from the existence of human recognition of the use of language in everyday social life. To carry out humanitarian duties, humans only have one tool, namely language. With language, humans can express what is on their minds. Something that has been felt to be the same and similar to it, does not necessarily feel similar, because it has not been revealed and revealed. Only with language can humans make something feel real and reveale Keywords: Language, Child, Comunication